2010
DOI: 10.1038/onc.2010.176
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of a DNA vaccine targeting the endothelial tip cell antigen delta-like ligand 4 in mammary carcinoma

Abstract: The Notch ligand delta-like ligand 4 (DLL4) is an essential component expressed by endothelial tip cells during angiogenic sprouting. We have described a conceptually novel therapeutic strategy for targeting tumor angiogenesis and endothelial tip cells based on DNA vaccination against DLL4. Immunization with DLL4-encoding plasmid DNA by in vivo electroporation severely retarded the growth of orthotopically implanted mammary carcinomas in mice by induction of a nonproductive angiogenic response. Mechanistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
3
19
1
Order By: Relevance
“…In total, this results in a mechanism in which tip-cells with low Notch-activity drive the branching of new vasculature, whereas stalk-cells with high Notch-activity drive the lengthening of the vessels. This mechanism is supported by multiple studies in which inhibition of Notch signaling during vascular development results in a hyper-branching phenotype (38)(39)(40)(41)43). Considering the known involvement on Notch in the process of angiogenesis, we speculated that hypoxic induction of JAG2 and its influence on Notch signaling could represent a novel mechanism for tumor-induced vasculogenesis.…”
Section: Discussionsupporting
confidence: 54%
“…In total, this results in a mechanism in which tip-cells with low Notch-activity drive the branching of new vasculature, whereas stalk-cells with high Notch-activity drive the lengthening of the vessels. This mechanism is supported by multiple studies in which inhibition of Notch signaling during vascular development results in a hyper-branching phenotype (38)(39)(40)(41)43). Considering the known involvement on Notch in the process of angiogenesis, we speculated that hypoxic induction of JAG2 and its influence on Notch signaling could represent a novel mechanism for tumor-induced vasculogenesis.…”
Section: Discussionsupporting
confidence: 54%
“…Pharmacological targeting of Dll4-Notch signaling in preclinical tumor models has been achieved by several different mechanisms including anti-Dll4 antibodies, DNA vaccination, soluble Dll4-Fc and Notch-Fc decoys, Notch antibodies, and γ-secretase inhibitors [24,28,30,31,37,41,67,68]. Unlike γ-secretase inhibitors that broadly block all Notch signaling, specific targeting of Dll4 with anti-Dll4 antibodies did not induce overt gastrointestinal toxicity and has thus emerged as an attractive target for anti-angiogenic cancer therapy [30,69].…”
Section: Introductionmentioning
confidence: 99%
“…Haller et al [42] reported on a xenogeneic cDNA vaccine encoding human DLL4, an essential component of tip cell integrity. Mice received 3 intradermal injections followed by in vivo electroporation.…”
Section: Delta-like Ligand 4 (Dll4)mentioning
confidence: 99%